2020
DOI: 10.1364/oe.403156
|View full text |Cite
|
Sign up to set email alerts
|

Optimal quantum phase estimation in an atomic gyroscope based on a Bose-Hubbard model

Abstract: We investigate the optimal quantum state for an atomic gyroscope based on a three-site Bose-Hubbard model. In previous studies, various states such as the uncorrelated state, the BAT state and the NOON state are employed as the probe states to estimate the phase uncertainty. In this article, we present a Hermitian operator H and an equivalent unitary parametrization transformation to calculate the quantum Fisher information for any initial states. Exploiting this equivalent unitary p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…then we can get the expressions of the above squeezed Schrödinger-cat states according to the fitting formulas in Eqs. (38)(39)(40). Specifically, for the SECS, Q ≈ 5.42 + 3.24N ; (43) for the SOCS Q ≈ −4.40N −1 − 3.01N − 1 2 + 1.28 + N ; (44) and for the SYSCS…”
Section: Phase Estimation With Squeezed Schr öDinger-cat Statesmentioning
confidence: 97%
See 1 more Smart Citation
“…then we can get the expressions of the above squeezed Schrödinger-cat states according to the fitting formulas in Eqs. (38)(39)(40). Specifically, for the SECS, Q ≈ 5.42 + 3.24N ; (43) for the SOCS Q ≈ −4.40N −1 − 3.01N − 1 2 + 1.28 + N ; (44) and for the SYSCS…”
Section: Phase Estimation With Squeezed Schr öDinger-cat Statesmentioning
confidence: 97%
“…To improve the estimation precision in the low-photonnumber regime, many quantum states (including N00N state [37], squeezed-entangled state [38], entangled even squeezed state [39], etc.) have been considered.…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 2, we compare the quantum Cramer-Rao bound of the NOON state [29], Entangled coherent state [30], Squeezed entangled state [10,31], QOOQ state [10], and our OI state (|Ψ in OI ) with the total input average photon number. We found that as long as the value of k is large enough, the state with the smallest quantum Cramer-Rao bound under the equal input total photon number is the OI state.…”
Section: A Quantum Parameter Estimation In the Mach-zehnder Interfero...mentioning
confidence: 99%
“…2 and Refs. [10,30,31], and all path-symmetric pure states can achieve their maximal phase sensitivity [32].…”
Section: A Quantum Parameter Estimation In the Mach-zehnder Interfero...mentioning
confidence: 99%